Generation of Monoclonal Antibodies against Ag85A Antigen of Mycobacterium tuberculosis and Application in a Competitive ELISA for Serodiagnosis of Bovine Tuberculosis - Xu, Zhengzhong; Hu, Ting; Xia, Aihong; Li, Xin; Liu, Ze; Min, Jingjing; He, Jingjing; Meng, Chuang; Yin, Yuelan; Chen, Xiang; Jiao, Xinan (Frontiers in Veterinary Science, 2017)
The Ag85 complex functions as the main secretory protein of Mycobacterium tuberculosis (M. tuberculosis) and BCG. This complex is comprised of the proteins, Ag85A, Ag85B and Ag85C, with Ag85A thought to play the largest role within the complex. However, the lack of commercially available monoclonal antibodies (mAb) against Ag85A still hinders the biological and applicative research on this protein. In this study, we developed and identified anti-Ag85A monoclonal antibodies, and five hybridoma cells were established. Using the indirect immunofluorescence test, we found that two anti-Ag85A mAbs did not cross-react with Ag85B and/or Ag85C. In addition, we showed that all of the mAbs tested in this study are able to react with endogenous Ag85A protein in BCG and rBCG::Ag85A using indirect ELISA and western blot analyses. A competitive ELISA (cELISA) based on mAb 3B8 was developed, the analyses of clinic serum samples from cattle with bovine tuberculosis and healthy cattle demonstrated that the sensitivity of the cELISA was 54.2% (26/48) and the specificity was 83.5% (167/200). This study demonstrated that the mAbs against Ag85A will provide useful reagents for further investigation into the function of the Ag85 complex and can be used for serodiagnosis of bovine tuberculosis.